Hopped up [videorecording (DVD)] : how Yakima Valley changed craft beer forever - Capelli, Tony; Carpenter, Tom; Carpenter, Steve; Goschie, Gayle (Dreamscape Media, LLC, 2021)
This documentary about hops and where they come from features the arid Yakima Valley where one-third of the world's hops are created by multigenerational farming families.